2015
DOI: 10.1051/0004-6361/201424073
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new transitional disk candidates in Lupus withHerschel

Abstract: Context. New data from the Herschel Space Observatory are broadening our understanding of the physics and evolution of the outer regions of protoplanetary disks in star-forming regions. In particular they prove to be useful for identifying transitional disk candidates. Aims. The goals of this work are to complement the detections of disks and the identification of transitional disk candidates in the Lupus clouds with data from the Herschel Gould Belt Survey. Methods. We extracted photometry at 70, 100, 160, 25… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 33 publications
2
36
3
Order By: Relevance
“…All of these YSOs fell within the coverage of the maps used, and 49 were detected in at least one Herschel band, 49 in PACS, and 19 in SPIRE. This leads to a Herschel detection rate of 18.77%±2.6%, which is much smaller than the percentage of detections obtained in similar studies in Chamaeleon (Ribas et al 2013) and Lupus (Bustamante et al 2015) of around 30%. Given that Ophiuchus is closer than those regions (150 ∼ 200 pc), the low detection rate is probably due to the higher background, which is emitting at mid-and long-IR wavelengths, and precludes the detection of faint objects.…”
Section: Detection Statisticscontrasting
confidence: 63%
See 1 more Smart Citation
“…All of these YSOs fell within the coverage of the maps used, and 49 were detected in at least one Herschel band, 49 in PACS, and 19 in SPIRE. This leads to a Herschel detection rate of 18.77%±2.6%, which is much smaller than the percentage of detections obtained in similar studies in Chamaeleon (Ribas et al 2013) and Lupus (Bustamante et al 2015) of around 30%. Given that Ophiuchus is closer than those regions (150 ∼ 200 pc), the low detection rate is probably due to the higher background, which is emitting at mid-and long-IR wavelengths, and precludes the detection of faint objects.…”
Section: Detection Statisticscontrasting
confidence: 63%
“…4 and A.1), we only find the 70 µm flux to be higher for some of the objects classified as transitional disks candidates. Hence, we cannot conclude that we have detected a trend in the transitional disk population, such as has been observed in previous investigations (Ribas et al 2013, Bustamante et al 2015. We also find the case of 2MASS J16285694-2431096 (#18), where the 70 µm flux is not only lower than the median SED, but lower than the third quartile.…”
Section: Study Of 70 Micron Fluxes In Transitional Diskscontrasting
confidence: 48%
“…The PACS sensitivity is sometimes shallower than the MIPS-2, resulting in a higher upper limit. For some targets, a more thorough data reduction of the PACS data was performed in other work (Ribas et al 2013;Olofsson et al 2013;Bustamante et al 2015). In Table 6 the derived fluxes and upper limits are compared.…”
Section: Long Wavelength Photometrymentioning
confidence: 99%
“…The availability of Spitzer IRS spectra between 5−35 µm was crucial for classification and determination of the hole size in these studies especially in covering the 8−20 µm region where the SEDs reach their minimum but is not well covered by the 8 and 24 micron photometry points. In recent years, far-infrared Herschel-PACS and SPIRE photometry has been used to identify and characterize (transition) disks (e.g., Ribas et al 2013;Bustamante et al 2015;Rebollido et al 2015). Other studies identified candidates by comparing the infrared part of their SEDs with the median T Tauri disk SED (e.g., Harvey et al 2007;Merín et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For the Herschel fluxes we adopt the most recent values presented by Bustamante et al (2015). The fluxes at wavelengths shorter than 24 μm were corrected for extinction by applying the dereddening relations listed in Cieza et al (2007).…”
Section: Photometrymentioning
confidence: 99%